Compliance Level of Supportive Care Needs Among Breast Cancer Survivor at Ibnu Sina Hospital Makassar - Muh. Zukri Malik; Kusrini Kadar; Ilhamjaya Patellongi (Indonesian Contemporary Nursing Journal, 2017)
Introduction: Survivor breast cancer who underwent supportive care have many unmet needs, they are also many reported having a poor quality of life. This study aims to assess and describe the level of fulfillment of supportive care breast cancer survivors. Method: This study used quantitative method with descriptive analytic approach. The number  of sample were  40 people came from the chemotherapy room and  and surgical treatment room of Ibnu Sina Hospital of Makassar, in the period of July 2016. The data were collected through  questionnaire of  Supportive Care Needs Survey Short Form 34 (SCNS-SF34) to assess the level of supportive care  survivors of breast cancer patients. Result: The results indicate that from  5 domains which need of  supportive care,there are  three domainsnot meeting the needs, namelypsychological,  information systems and health, and the third is support and care needs. While the fulfilled needs are physical, daily activities and sexual need. There are 80% of breast cancer survivors undergoing bad life quality and only 20%  undergo  good quality of life. Conclucion: The fulfilment level of supportive care survivors of   breast cancer needs generally are not met, the highest needfound is psychological need domain.